2013
DOI: 10.1016/j.epag.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in primary school children in Port Said city

Abstract: Background: The highest prevalence rates of childhood obesity have been observed in developed countries, however, its prevalence is increasing in developing countries as well. Objectives: To estimate the prevalence of overweight and obesity among primary school children, aged from 6 to 12 years and to estimate risk factors of obesity and overweight, defined by body mass index (BMI). Methods: A cross-sectional study was carried out at Port Said city during the second term of school year 2010/2011. The researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
27
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 15 publications
(13 reference statements)
11
27
3
Order By: Relevance
“…This was similar with study done in Brazil [44], Ghana [16], Ghana and Uganda [22]. Several other studies conducted in Ghana [46], Egypt [5] and Ethiopia [4] found that vigorous intensity sports reduced risk of overweight and obesity. But other studies in Lithuania [47] and Romania [40] reported that any physical activities were not associate with reduction of the risk of increased overweight.…”
Section: Discussionsupporting
confidence: 90%
“…This was similar with study done in Brazil [44], Ghana [16], Ghana and Uganda [22]. Several other studies conducted in Ghana [46], Egypt [5] and Ethiopia [4] found that vigorous intensity sports reduced risk of overweight and obesity. But other studies in Lithuania [47] and Romania [40] reported that any physical activities were not associate with reduction of the risk of increased overweight.…”
Section: Discussionsupporting
confidence: 90%
“…The high prevalence of overweight and obesity in our study ( Figure 1) agrees to some extent with values described by a recent Egyptian study in primary school children which reported 17.7% and 13.5% for overweight and obesity respectively [20]. It also agrees with findings from a survey developed and administered by the World Health Organization (WHO) and the Center for Disease Control (CDC) and was conducted in 7 African countries.…”
Section: Discussionsupporting
confidence: 81%
“…Because body proportions normally change during childhood and pubertal development, the body mass index (BMI) measurement in children and adolescents was defined as the individual's body weight divided by the square of their height in meters (kg/m 2 ); values greater than the 85th percentile and less than the 95th percentile or greater than the 95th percentile for age and sex were considered as overweight or obesity, respectively, when compared with the Standard Egyptian growth charts [29][30][31]. Subjects were then classified according to the threshold BMI z score adjusted for age and sex; moderately obese (z score of 2.0-2.5) or severely obese (z score [ 2.5) [32].…”
Section: Study Populationmentioning
confidence: 99%